Analysis of Audit Tenure, CEO Education, And Ineffective Monitoring On Fraudulent Financial Statement - Rochmah, Umi Nur Fryda Kusli; Budiwitjaksono, Gideon Setyo (E-Jurnal Akuntansi, 2025)
The study explores the impact of audit tenure, CEO education, and ineffective monitoring on fraudulent financial statements in BUMN companies listed on the Indonesia Stock Exchange from 2021 to 2023. The methodology used is a quantitative approach by panel data regression in 19 BUMN companies. Data were collected through documentation of annual reports and analyzed using E-views 12. Fraudulent financial statements are proxied by the Beneish M-Score. Research findings show that audit tenure and ineffective monitoring have no significant effect, CEO education has a significant negative impact on fraudulent financial statements. Simultaneously, the three variables have a considerable influence on fraudulent financial statements. These findings indicate that CEO's education rank has an important role in preventing financial statement fraud. Keywords: Audit Tenure, CEO Education, Fraudulent Financial Statement, Ineffective Monitoring.